2021
DOI: 10.1101/2021.02.24.432750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Condensation of theDrosophilaNerve Cord is Oscillatory and depends on Coordinated Mechanical Interactions

Abstract: During development, organs must form with precise shapes and sizes. Organ morphology is not always obtained through growth; a classic counterexample is condensation of the nervous system during Drosophila embryogenesis. The mechanics underlying such condensation remain poorly understood. Here, we combine in toto live-imaging, biophysical and genetic perturbations, and atomic force microscopy to characterize the condensation of the Drosophila ventral nerve cord (VNC) during embryonic development at both subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Although we are not aware of a experimental setup that may directly verify the bounds encountered, recent measurements of Drosophila condensation have correlated decaying deformation oscillations with a reduction in tissue viscosity (Karkali et al 2021), confirming the relation between oscillatory regime and visco-elastic material properties.…”
Section: Preliminary Discussion and Experimental Comparisonmentioning
confidence: 58%
“…Although we are not aware of a experimental setup that may directly verify the bounds encountered, recent measurements of Drosophila condensation have correlated decaying deformation oscillations with a reduction in tissue viscosity (Karkali et al 2021), confirming the relation between oscillatory regime and visco-elastic material properties.…”
Section: Preliminary Discussion and Experimental Comparisonmentioning
confidence: 58%
“…Recent work has demonstrated that VNC condensation can be well described as a viscoelastic process, which generates oscillations in tissue length during condensation because of differences in the timescales over which the different mechanical interactions occur ( 41 ). Our work here shows that the VNC appears to only weakly scale with embryo length but does display evidence of a minimal viable size.…”
Section: Discussionmentioning
confidence: 99%
“…The hindgut offers an opportunity to test whether chiral tissues scale and, if so, whether they scale equally along different axes. The VNC is a unique organ that spans across the entire embryo length before condensing by means of apoptosis and long-range coordinated mechanical interactions ( 40 , 41 ). As the VNC shrinks, rather than grows, to its final size within the embryo, its mechanisms of size control are likely distinct from well-studied systems such as the Drosophila wing disk ( 12 ).…”
Section: Introductionmentioning
confidence: 99%